Immune thrombocytopenia in the aspect of multiple primary neoplasms - R. V. Vardanyan; S. G. Zakharov; T. A. Mitina; P. A. Zeynalova; Yu. Yu. Chuksina; A. V. Zakharova (Онкогематология, 2023)
Multiple primary malignant neoplasms (MPMNs) is a complex process in which the development of 2 or more neoplasms simultaneously or after a certain interval is observed. MPMNs develop independently from each other within one or more organs. Many etiopathogenetic factors can cause MPMNs. Numerous studies have been conducted to study the effect of T-cell immunity on the development of this pathology. Today, there is a steady upward trend in the prevalence of mpmns, which, on the one hand, is due to more effective methods of early diagnosis, an increase in patient overall survival, and early antitumor therapy (chemotherapy, radiation therapy), on the other hand, this trend may be associated with pathology of T-regulatory cellular immunity. T-regulatory cells play a strategic role in the development of immune homeostasis, and their function is closely related to the occurrence of a wide range of pathologies, including autoimmune diseases and malignant neoplasms. The article presents a clinical case of a patient with a confirmed diagnosis: mpmn, immune thrombocytopenia (idiopathic thrombocytopenic purpura). On prednisolone therapy, remission was achieved for 2 metachronous tumors and a complete hematological response for immune thrombocytopenia was obtained. there were no signs of hemorrhagic syndrome and complications during prednisone therapy. It is planned to continue monitoring the patient for metachronous tumors by a hematologist, an oncologist at the place of residence, as well as at the center for orphan diseases of the Moscow Regional Research Clinical Institute named after M. F. Vladimirsky with control of platelets and general condition.